Septic arthritis in malignancy - Bambang Setiyohadi; D Santosa; Titis Titis; A A Abdullah (Indonesian Journal of Rheumatology, 2011)
Septic arthritis is an infection of a joint, which canbe caused by bacteria, viruses, fungi, or parasites. The infection may happen in distant sites of the body, which then spread hematogenously, or it could also result from open wounds, surgery, or unsterile injections.1 Septic arthritis is a serious condition that, if left undiagnosed and untreated, can cause joint destruction and an irreversible loss of joint function.2,3 Based on epidemiological data, the incidence of septic arthritis in general population is 2–10 cases in 100,000 people annually and is increased in those who have risk factors for septic arthritis, such as rheumatoid arthritis (RA) and joint prosthesis. In those with RA, the incidence of septic arthritis rises up to 30–70 cases in 100,000 people annually, and in those with prosthesis the figure is around 40–68 cases in 100,000 people annually.4,5 Septic arthritis can affect all age groups, but it is more prevalence in the elderly and in children under 5 years old, in which the prevalence is 8.4 and 5 cases, respectively, in 100,000 people annually.5 Septic arthritis is usually monoarticular, whereas polyarticular involvement occurs in only 10–15% of cases. The knee is involved in around 50% of cases.Septic arthritis is still a challenge for cliniciansince there has not been a significant decline in both morbidity and mortality in the last two decades.2 Late recognition and therapy can cause permanent joint dysfunction and even death; thus, early diagnosis and prompt therapy is expected to decrease the morbidity and mortality rate in septic arthritis.6 In this case report we would like to present a case of a woman suffering from septic arthritis with an underlying immunocompromised condition of malignancy